Bioinformatic analysis of neuropeptide and receptor expression profiles during midgut metamorphosis in Drosophila melanogaster. - Bowser, P.R.; Tobe, S.S. (Peptides, 2006)
Neuropeptides are important messenger molecules in invertebrates, serving as neuromodulators in the nervous system and as regulatory hormones released into the circulation. Understanding the function of neuropeptides will require the integration of genetic, biochemical, physiological and behavioral information. The advent of DNA microarrays and bioinformatic databases provides a wealth of data describing the expression profiles of thousands of genes during biological processes. One such array catalogs the developmental patterns of gene expression during the metamorphic transformation of the Drosophila midgut. We have mined the data from this experiment to explore changes of expression in genes coding for known neuropeptides, peptide hormones, and their receptors during the metamorphosis of the midgut. We found small but significant changes in the expression of the peptides diuretic hormone, FGLa-type allatostatins, myoinhibiting peptide, ecdysis-triggering hormone, drosokinin and the burs subunit of bursicon, as well as the receptors DAR-2, NPFR1, ALCR-2, Lkr and DH-R. Just as advances have been made in understanding the molecular basis of invertebrate neuropeptide action by analysis of genome projects, data mining of gene expression databases can help to integrate molecular, biochemical and physiological knowledge of biological processes.